Trenutne smeri razvoja pri spajanju materialov v avtomobilski industriji - Tušek, Janez (Strojniški vestnik, 2004)
This paper describes the current state of the field of material joining in theworldćs automotive industry. The processes of material joining that are used in the biggest automotive factories are theoretically described and confirmed with practical examples. Resistance spot welding, arc welding, brazing, hybrid welding, stud welding, adhesive bonding and mechanical joiningare described. We conclude that the future of material joining in the automotive industry is likely to be in the use of laser beams for welding and brazing, adhesive bonding and in mechanical joining with or without rivets.
Keywords: spajanje materialov; varjenje; spajkanje; lepljenje; automotive industry; avtomobilska industrija